Variations in Perceptions of Well-Being within Families of Youths with Intellectual Disabilities in Saudi Arabia - Ghaleb H. Alnahdi (MDPI AG, 2024)
This study investigates the family well-being among Saudi Arabian families with youth who have an intellectual disability. A sample of 148 family members, including parents and other relatives, was surveyed on emotional well-being, family interactions, and parenting. This study aimed to explore the unique challenges and dynamics within these families, providing insights into how an intellectual disability in a youth affects the family unit. The research highlights a gap in understanding the specific impacts of intellectual disability on family life in the Saudi context. Key findings include variations in family quality of life perceptions among different family members, with fathers showing distinct levels of satisfaction. This study contributes to the development of culturally sensitive support strategies and policies, emphasizing the need for targeted interventions to enhance the well-being of these families in Saudi Arabia.